Methotrexate, blood pressure and markers of arterial function in patients with rheumatoid arthritis: a repeated cross-sectional study. (September 2017) - Mangoni, Arduino A.; Baghdadi, Leena R.; Shanahan, E. Michael; Wiese, Michael D.; Tommasi, Sara; Elliot, David; Woodman, Richard J.
Background: Methotrexate (MTX) treatment in rheumatoid arthritis (RA) has been associated with lower cardiovascular risk compared to other disease-modifying antirheumatic drugs (DMARDs). We sought to identify whether the MTX-associated cardioprotection involves changes in blood pressure (BP) and/or arterial function. Methods: Clinic and 24-hour peripheral and central systolic and diastolic BP (SBP and DBP), augmentation index (AIx), pulse wave velocity (PWV) and plasma asymmetric dimethylarginine (ADMA) were assessed in RA patients on stable treatment with either MTX ± other DMARDs (MTX group, n = 56, age 61 ± 13 years, 70% females) or other DMARDs (non-MTX group, n = 30, age 63 ± 12 years, 76% females). Measurements were performed at baseline and after 8 months. Results: After adjusting for visit, age, gender, body mass index, folic acid use and 28-joint disease activity score, the MTX group had significantly lower clinic peripheral SBP (−7.7 mmHg, 95% CI −13.2 to −2.3, p = 0.006) and DBP (−6.1 mmHg, 95% CI −9.8 to −2.4, p = 0.001) and clinic central SBP (−7.8 mmHg, 95% CI −13.1 to −2.6, p = 0.003) and DBP (−5.4 mmHg, 95% CI −9.1 to −1.6, p = 0.005) versus the non-MTX group. Furthermore, the MTX group had significantly lower 24-hour peripheral and central SBP and DBP and PWV versus the non-MTX group ( p < 0.01 for all comparisons). By contrast, there were no significant between-group differences in AIx and ADMA. Conclusions: RA patients on MTX treatment had significantly lower clinic and 24-hour peripheral and central BP compared to those who did not take MTX. The lower BP with MTX may be related to differences in PWV, but not in AIx or ADMA concentrations. Further longitudinal studies including randomized controlled trials are warranted to confirm these findings, to identify other possible mechanisms responsible for the effects of MTX on BP and PWV, and to establish whether these effects might account for the reduced cardiovascular risk with MTX.